Psycho-social impact of tooth loss among Teenagers - Raynor FAVIANOZAKI; Isya HANIN (Journal of Syiah Kuala Dentistry Society, 2022)
Psycho-social is a reciprocal relationship between psychological and social aspects in humans, whichplays an essential role in the individual's cognitive abilities and social interactions. Psycho-social impacts arechanges in humans, including psychological and social aspects triggered by external changes such as changes indental aesthetics. Tooth loss certainly impacts one's aesthetics, especially among young adults living in the age ofsocial media, where aesthetics is necessary. This study describes the psycho-social impact of tooth loss in youngadults. This study is a descriptive observational study with a cross-sectional design. This research was conducted bydistributing the Psycho-social Impact of Dental Aesthetic Questionnaire to 120 people who suffered from tooth lossat Trisakti University, campus A, Jakarta. Of the 66 men and 54 women, the average PIDAQ score for men was 75.87and for women was 80.9. The psycho-social impact of tooth loss on young adult women is more significant than thatof men in the same age group.KEYWORDS: Psycho-social impact, PIDAQ, Young Adult, Tooth loss